2016
DOI: 10.1212/wnl.0000000000002502
|View full text |Cite
|
Sign up to set email alerts
|

Structural network efficiency predicts conversion to dementia

Abstract: These results support a role of network disruption playing a pivotal role in the genesis of dementia in SVD, and suggest network analysis of the connectivity of white matter has potential as a predictive marker in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 25 publications
10
84
0
Order By: Relevance
“…Consistent with earlier studies, the global and local efficiency of the connectome was associated with WMH volume (Lawrence et al, 2014;Tuladhar, van Dijk, et al, 2016;Tuladhar, van Uden, et al, 2016;Valenti et al, 2017;Wiseman et al, 2018;Xu et al, 2018). Consistent with earlier studies, the global and local efficiency of the connectome was associated with WMH volume (Lawrence et al, 2014;Tuladhar, van Dijk, et al, 2016;Tuladhar, van Uden, et al, 2016;Valenti et al, 2017;Wiseman et al, 2018;Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with earlier studies, the global and local efficiency of the connectome was associated with WMH volume (Lawrence et al, 2014;Tuladhar, van Dijk, et al, 2016;Tuladhar, van Uden, et al, 2016;Valenti et al, 2017;Wiseman et al, 2018;Xu et al, 2018). Consistent with earlier studies, the global and local efficiency of the connectome was associated with WMH volume (Lawrence et al, 2014;Tuladhar, van Dijk, et al, 2016;Tuladhar, van Uden, et al, 2016;Valenti et al, 2017;Wiseman et al, 2018;Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…DTI tractography was used to generate white matter tracts (Behrens & Jbabdi, 2009). As a control, we assessed the association between WMH volume with global and local efficiency which has been described in prior studies (Lawrence et al, 2014;Tuladhar, van Dijk, et al, 2016;Tuladhar, van Uden, et al, 2016;Valenti et al, 2017;Wiseman et al, 2018;Xu et al, 2018). For the first time, we correlated the CVR of gray and white matter with the global and local efficiency of the connectome while adjusting for age, gender, WMH volume, and gray matter volume.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been demonstrated in both sporadic SVD and CADASIL patients that the forceps minor and the thalamic radiation are strategic WM tracts for processing speed. 29,30 O'Sullivan et al 13 demonstrated that in SVD patients DTI indices, especially in NAWM, correlated more strongly with cognitive function than T2-lesion volume, after controlling for conventional MRI parameters. Similarly, diffusion changes predict faster decline in psychomotor speed, executive functions, and working memory regardless of conventional MRI findings.…”
Section: June 2016mentioning
confidence: 99%
“…3) [45], [46], [44]. Lower connectivity within cerebral networks was associated with cognitive impairment and dementia [47], [48]; WMHs were associated with less brain activation in the frontal cortex on fludeoxyglucose-positron emission tomography [49], [50], [51]. Mood disorders and apathy are common after stroke, affect cognitive test performance (and more fundamentally, patient participation in research), and may reflect impaired connectivity.…”
Section: Resultsmentioning
confidence: 99%